(untitled) (Acta Scientiarum. Biological Sciences, 2016)
This study describes variation in ontogenetic development of the parthenogenetic scorpion Tityus stigmurus based on variations in size, intermolt period, and number of instars. Individuals were created under laboratory conditions (28 ± 3ºC) and subjected to similar diet regime. Comparative measurements of carapace, segment V of the metasoma, and the movable finger are used to estimate variations in size among instars. The application of Dyar rule shows a growth factor from 1.14 to 1.38 depending on the parameter analysed with intense variations in size between and within the different instars. The duration of the period from birth to adulthood was 871 days, after six moults. These data suggest that T. stigmurus has the longest post-embryonic development of Tityus genus and the existence of an extra molt to reach maturity.